You should use the fundamental formula of trigonometry `1 - cos^2 theta = sin^2 theta` such that:

`2 - 2(1 - cos^2 theta) = cos theta`

Opening the brackets yields:

`2 - 2 + 2cos^2 theta = cos theta`

Reducing like terms such that:

`2cos^2 theta = cos theta`

Moving...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You should use the fundamental formula of trigonometry `1 - cos^2 theta = sin^2 theta` such that:

`2 - 2(1 - cos^2 theta) = cos theta`

Opening the brackets yields:

`2 - 2 + 2cos^2 theta = cos theta`

Reducing like terms such that:

`2cos^2 theta = cos theta`

Moving all terms to one side yields:

`2cos^2 theta- cos theta = 0`

You should factor out `cos theta` such that:

`cos theta(2cos theta - 1) = 0`

You need to solve the following equations such that:

`cos theta = 0 => theta = pi/2 and theta = 3pi/2`

`2 cos theta - 1 = 0 => cos theta = 1/2 => theta = pi/6 and theta = 2pi - pi/6 => theta = 11pi/6`

**Hence, evaluating the solutions to the given equation yields `theta = pi/6 , theta = pi/2 , theta = 3pi/2` and `theta= 11pi/6.` **